On Certain Subclass of Analytic Functions Involving Generalized Derivative Operator (Global Journal of Science Frontier Research, 2014)
In this paper, a new subclass of analytic functions is introduced by means of a generalized derivative operator. Several properties like coefficient inequalities, growth and distortion theorems, convex linear combinations and radii of close-to-convexity, starlikeness and convexity of analytic functions belonging to the subclass are investigated.
Keywords: analytic function; starlike function; generalized derivative operator; coefficient inequalities; extreme points